Studies on Methane Gas Hydrate Formation Kinetics Enhanced by Isopentane and Sodium Dodecyl Sulfate Promoters for Seawater Desalination - Omar Bamaga; Iqbal Ahmed; Asim M. Wafiyah; Mohammed Albeirutty; Hani Abulkhair; Amer Shaiban; Praveen Linga (Energies, 2022)
Methane hydrate applications in gas storage and desalination have attracted increasing attention in recent years. In the present work, the effect of isopentane (IP), sodium dodecyl sulfate (SDS), and IP/SDS blends as promoters on methane hydrate formation kinetics, in terms of the pressure–temperature (P-T) profile, gas uptake, hydrate induction time (HIT), and water-to-hydrate conversion ratio (WHCR), were studied for distilled water and seawater samples with an IP/water sample ratio of 3:10 (by volume) and an SDS/water sample ratio of 1:1000 (by mass). Each solution was tested in a stirred tank at 600 rpm at a temperature and pressure of 2 °C and 5.2–5.3 MPa. In the case of methane hydrate formation in distilled water, the highest WHCR attained was 9.97% without additives, and 45.71% and 72.28% for SDS and isopentane additives, respectively. However, when using seawater at a salinity of 3.9%, the highest WHCR attained was 2.26% without additives and 9.89% and 18.03% for SDS and IP promoters, respectively, indicating the inhibiting effect of salinity on hydrate formation. However, the HIT was longer for seawater hydrate formation, with an average of 13.1 min compared to 9.90 min for methane hydrate formation. Isopentane enhances the HIT for methane hydrate formation in seawater by 2.23 times compared to SDS. For methane hydrate formation in seawater, the presence of IP shortened the HIT by 15.6 min compared to the seawater sample without promoters. Additionally, a synergistic effect was observed when IP and SDS were combined and used in methane hydrate formation in distilled water and seawater systems. The positive effect of IP on methane hydrate formation is possibly due to the binary hydrate formation mechanism, which improves the hydrate formation thermodynamic and kinetic parameters.